On Certain Types of Neutrosophic Fuzzy Graphs - Alias B. Khalaf; Prithivirajan Padma (Pan-American Journal of Mathematics, 2022)
In this paper, we introduce some types of NF graphs and operations. Also we define the partial NF subgraph, spanning NF subgraph, strong degree of the vertex, total strong degree of the vertex and its properties are included.